Research Progress on Structure and Anti-Gynecological Malignant Tumor of Shikonin - Ke, Li-Na; Kong, Ling-Qi; Xu, Huan-Huan; Chen, Qin-Hua; Dong, Yun; Li, Bin; Zeng, Xiao-Hua; Wang, Hong-Mei (Frontiers in Chemistry, 2022)
Gynecological malignancy always endangers women's health. Shikonin is a naphthoquinone compound with a variety of biological activities. Studies have shown that shikonin can inhibit cell proliferation, promote cell apoptosis and induce cell necrosis. In recent years, studies on shikonin in gynecological malignant diseases are also increasing. Therefore, we reviewed the mechanism of action and structure optimization of shikonin in gynecological malignant tumors, in order to provide reference for further research and related drug development.